2011
DOI: 10.1017/s1751731110002594
|View full text |Cite
|
Sign up to set email alerts
|

Validating indicators of sheep welfare through a consensus of expert opinion

Abstract: A consensus of expert opinion was used to provide both face and consensual validity to a list of potential indicators of sheep welfare. This approach was used as a first step in the identification of valid welfare indicators for sheep. The consensus methodology of the National Institute of Health, using pre-meeting consultation and focus group discussions, was used to ascertain the consensus opinion of a panel of sheep welfare experts. The Farm Animal Welfare Council's five freedoms were used as a framework to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
89
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(93 citation statements)
references
References 32 publications
3
89
0
1
Order By: Relevance
“…Since before their participation in this study not all observers were familiar with the assessment of eye conditions, the high level of diagnostic performance may reflect both the clear scoring scales used, and the ease of identifying lambs with ocular discharges and lesions. The presence of entropion was considered to be a particular on-farm welfare issue for young lambs by an expert panel in Great Britain (Phythian et al, 2011a) and Scandinavia (Ulvund, 2012). This was supported by the study results that identified over 6% of the study population had an ocular abnormality; most frequently diagnosed as entropion.…”
Section: Trained Observersmentioning
confidence: 69%
See 3 more Smart Citations
“…Since before their participation in this study not all observers were familiar with the assessment of eye conditions, the high level of diagnostic performance may reflect both the clear scoring scales used, and the ease of identifying lambs with ocular discharges and lesions. The presence of entropion was considered to be a particular on-farm welfare issue for young lambs by an expert panel in Great Britain (Phythian et al, 2011a) and Scandinavia (Ulvund, 2012). This was supported by the study results that identified over 6% of the study population had an ocular abnormality; most frequently diagnosed as entropion.…”
Section: Trained Observersmentioning
confidence: 69%
“…This work has been previously described (Phythian et al, 2011a). Briefly, the experts selected animal-based welfare indicators that were considered to be sensitive to current on-farm welfare issues for lambs in Great Britain.…”
Section: Animal-based Indicatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies report those indicators that have been used to analyse farm sustainability (Coffey et al, 2004;Nahed et al, 2006;Galá n et al 2007;Peacock and Sherman, 2010); animal welfare (Napolitano et al, 2009;Phythian et al, 2011), environmental effects, animal welfare and milk quality of organic farms (Mü ller-Lindenlauf et al, 2010), and differences, in general, between organic and conventional farms (Nauta et al, 2006;Rozzi et al, 2007). Other studies evaluate the technical and economic performance of organic farming ).…”
Section: Introductionmentioning
confidence: 99%